Project-Based Learning Method and Academic Performance of Secondary School Biology Students in Ogbia Local Government Area, Bayelsa State, Nigeria - Martha Ijok Adibe Njoku; Miriam Chiwendu Okoro (International Journal on Integrated Education, 2026)
Biology is a science subject that require hands-on practical experience for better understanding and high academic performance. Unfortunately, Biology teachers are still searching for the appropriate instructional method that will produce the desired result. This led to the study that investigated the effect of Project-Based Learning (PBL) method on the academic performance of secondary school Biology students in Ogbia Local Government Area, Bayelsa State. The research employed a quasi-experimental pretest-posttest control group design involving 77 Senior Secondary School Two (SS2) students from two intact classes in two public secondary schools. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. The Biology Performance Test (BPT) served as the instrument for data collection. The Kuder-Richardson formula 20 (KR-20) was used to determine the internal consistency of the multiple-choice items and a reliability coefficient of 0.76 Data were analyzed using descriptive statistics (means and standard deviations) and inferential statistics (Analysis of Covariance - ANCOVA). The findings revealed that students taught Biology using project-based learning method achieved significantly higher performance (mean gain = 20.15) compared to those taught using traditional lecture method (mean gain = 13.88), with F(1,74) = 651.242, p < 0.05. Additionally, the study found no significant influence of gender on academic performance when project-based learning was used, with male students scoring a mean of 30.00 and female students scoring 30.66, F(1,32) = 0.145, p > 0.05. The study concluded that project-based learning is significantly more effective than traditional methods in enhancing Biology academic performance and creates gender-inclusive learning environments. It was recommended that Biology teachers should adopt project-based learning approaches in their instructional practice, as this study has demonstrated its effectiveness in significantly improving student academic performance.